A feminist figuration from the interior focus in the story “The child and the morning” by Laura Riesco - Mitma Chávez, Daniel Enrique (2022)
This article will analyze the story El niño y la mañana by the Peruvian writer Laura Riesco. Inner focus will be studied in it, a theory developed by the Frenchman Gerard Genette that proposes a narrator circumscribed to the consciousness of a character. In addition to Genette, the studies of Mieke Bal, Seymour Chatman, José Valles Calatrava and Eric Rundquist will be taken. Likewise, how this perspective allows us to know the subtext that exists behind the story. This will be seen from the postulates of Ernest Hemingway who developed this in his Iceberg theory and the writers Ricardo Piglia and Juan Villoro. Finally, in that subtext that keeps the story, the feminist discourse embodied in the main character will be deepened. This will be analyzed from the perspective of the French philosopher Gilles Lipovetsky and the theory of the Third Woman together with the studies of Mariemma Mannarelli and Cyinthia Enloe.